Micropropagation and storage of Plectranthus amboinicus (Loureiro) Sprengel shoot apices for germplasm conservation - Arumugam, Greetha (2018)
Plectranthus amboinicus is a valuable medicinal plant under threat due to indiscriminate collection. This study communicates a reproducible micropropagation method and complimentary conservation strategy for a sustainable utilisation of this herb. For micropropagation, ideal growth of apical and axillary buds of P. amboinicus under in vitro culture conditions observed on semi-solid MS media supplemented with 0.4 mg l-1 BAP. Rooting of shoot cultures observed on half-strength semi-solid MS media producing 12.47 ± 0.35 roots per explant. Further, acclimatisation of rooted cultures on peat-moss moistened with sterile MS media produced 76.7 ± 5.8% survival. Subsequent, EO analysis identified carvacrol as major constituent at 43.3% in field grown and 45.1% micropropagated samples. This efficient micropropagation system permits mass propagation of P. amboinicus and ensures continuous supply of raw materials to various industries. For conservation of P. amboinicus, encapsulation conditions were optimised enabling easier germplasm exchange while providing protection towards pretreatments of short- and long-term conservation protocols. Optimisation of encapsulation conditions with 3% (w/v) sodium alginate in 100 mM CaCl2 solution was found ideal and employed in further studies. Standardisation of in vitro shoot tips of 3-5 mm size dissected from 1st or 2nd subcultures were chosen exhibiting 100.0 ± 0.0% survival with 4.9 ± 0.2 shoots per explant desirable for conservation studies. Nodal segments exhibiting poor regeneration were not preferred for conservation. Encapsulated shoot tips exhibited superior conversion frequency when inoculated on agar (78%) followed by peat-moss (58%) and cotton (38%). While, in short-term storage conditions, synthetic seeds of P. amboinicus stored up to 30 days at 4°C retained 77% survival rate. In cryopreservation, sucrose preculture is a prerequisite for protocol optimisation. Sucrose preculture between 0.25 to 0.5 M greatly enhanced tolerance of shoot tips towards dehydration and freezing. Succeeding, encapsulation-dehydration method establishment, in vitro grown shoot tips of P. amboinicus were precultured in 0.4 M sucrose for 24 hrs, encapsulated in 3% ca-alginate matrix and subjected silica gel desiccation for 12 hrs and cryopreserved produced finest post thaw recovery with 50.0 ± 5.8% survival and 36.7 ± 5.8% regrowth. Meanwhile, encapsulation-vitrification technique gave up to 57% survival and 37% regrowth when in vitro shoot tips were precultured in 0.4 M sucrose (24 hrs), followed by 3% ca-alginate matrix coating, loaded with L1 (0.4 M sucrose + 1.0 M glycerol) or L3 (0.4 M sucrose + 1.0 M glycerol + 5% (w/v) DMSO) for 40 mins, and dehydrated with PVS2 (30% (w/v) glycerol, 15% (w/v) EG, 15% (w/v) DMSO) for 20 mins and exposed to liquid nitrogen. In both techniques encapsulated shoot tips were dehydrated to an average of 35 to 36% moisture content through either direct (silica gel) or chemical (cryoprotectants) dehydration before freezing exhibited average regeneration suggesting P. amboinicus could be extremely cold-sensitive. Further, histological analysis on cryopreserved P. amboinicus shoot tips revealed appropriate pretreatments are essential to provide maximal protection and induce tolerance during exposure to ultra-low temperatures. To the best our knowledge, this is the first report on P. amboinicus cryopreservation by vitrification-based techniques, which would provide a wider platform for propagation and conservation of tropical herbal germplasms of Malaysia.